Body mass index and treatment response to subcutaneous abatacept in patients with psoriatic arthritis: a post hoc analysis of a phase III trial. Issue 1 (30th May 2019) - McInnes, Iain B; Ferraccioli, Gianfranco; D'Agostino, Maria-Antonietta; Le Bars, Manuela; Banerjee, Subhashis; Ahmad, Harris A; Elbez, Yedid; Mease, Philip J
Abstract : Objective: This post hoc analysis of the phase III Active PSoriaTic Arthritis RAndomizEd TriAl (ASTRAEA) evaluated the effect of baseline body mass index (BMI) on subsequent response to subcutaneous (SC) abatacept in patients with psoriatic arthritis (PsA). Methods: In ASTRAEA, patients with active PsA were randomised (1:1) to receive blinded weekly SC abatacept 125 mg or placebo for 24 weeks. Treatment response at week 24 was assessed by the proportions of patients achieving American College of Rheumatology 20% improvement response, Disease Activity Score in 28 joints (DAS28 (C reactive protein (CRP))) ≤3.6 and <2.6, Health Assessment Questionnaire-Disability Index reduction from baseline ≥0.35 and radiographic non-progression (defined as change from baseline ≤0 in PsA-modified total Sharp/van der Heijde score). Responses were stratified by baseline BMI (underweight/normal, <25 kg/m 2 ; overweight, 25–30 kg/m 2 ; obese, >30 kg/m 2 ) and compared in univariate and multivariate models. Results: Of 212/213 and 210/211 patients with baseline BMI data in the abatacept and placebo groups, respectively, 15% and 19% were underweight/normal, 36% and 27% were overweight, and 49% and 54% were obese. After adjusting for baseline characteristics, there were no significant differences for any outcome measure at week 24 with abatacept in the overweight or obese versus underweight/normal subgroup. In the placebo group, patients in the obese versus underweight/normal subgroup were significantly less likely to achieve DAS28 (CRP) <2.6 at week 24 (OR 0.26; 95% CI 0.08 to 0.87; p=0.03). Conclusion: BMI does not impact clinical or radiographic response to SC abatacept in patients with PsA. Trial registration number: NCT01860976 .